The Integrating the SETS (Science, Environment, Technology, Society) Framework into E-Worksheets for Natural Resource Education - Rafida Ramania Sahri; Purwanto; Supriono; Chanifah; Solikhin (CV Bumi Spasial, 2025)
In the 21st century, students must have thinking skills and active learning to realize quality education. While this requires effective learning resources, existing traditional worksheets are often limited to memorization, failing to support the development of these essential skills. The purpose of this development research is to produce an e-LKPD product with a SETS approach to the material of natural resource potential. The method used in this development research is Research and Development (R&D) with the 4D model (Define, Design, Development, and Disseminate). The type of data uses quantitative descriptive analysis techniques with data collection using questionnaires. The feasibility test stage in the form of material validation obtained a result of 82% with feasible criteria and design validation obtained a result of 95% with very feasible criteria. The results of the trial in class XI.12 State Senior High School Bululawang 1, obtained a result of 86% with very good criteria. This high positive response indicates the e-LKPD’s potential to enhance student engagement, a key factor in improving educational quality and fostering active thinking skills. Based on these results, the SETS-based e-LKPD product is concluded to be feasible for implementation, offering a practical tool to foster 21st-century skills and providing a basis for further application and research in broader contexts.